The perceptions of people towards Urban Transformation Centre (UTC) / Chandy Rhia Ubong and Urai Tumbai - Ubong, Chandy Rhia; Tumbai, Urai (2014)
Urban Transformation Centre (UTC) is one of the government programme where the aims of UTC is to provide the urban areas or community better services along with a government function, private sector and non-government in one building. This study are conducted to examine the perception of people towards Urban Transformation Centre (UTC), to identify the relationship between perception level of people towards UTC and personality and attitude of employees and to investigate the correlation between perception level of people towards UTC and quality of facilities. This research is conducted by using a simple random sampling technique where the elements in the population are selected randomly. The sample sizes for the purpose of this research are 150 respondents selected randomly in UTC at Kota Kinabalu, Sabah. While the data collection instrument for this research is done through questionnaires and interviews.